THE USE OF HARDWARE AND SOFTWARE ARDUINO IN INNOVATION ACTIVITY OF FUTURE PHYSICS TEACHERS AND STUDENTS - Andreev, А.М.; Kulinich, А.Г. (Journal of Information Technologies in Education (ITE), 2017)
The article considers the problem of using information tools in educational and scientificresearch activity of future Physics teachers and students. The place of information technology in the process of training future teachers of Physics to innovative organizations activities of students are associated with basic blocks: information training of students – future teachers of Physics; the use of information technology by students in their educational and research activities; development, approbation and implementation new information and communication products in the educational process. This article is devoted to the second and third of these directions. The educational opportunities of hardware-software complex Arduino were researched and tested at experimental training of students – future teachers of Physics Zaporizhzhya National University (in the framework of the discipline “Fundamentals of Modern Eelectronics”, “Computerization of School Physical Experiment”, as well as at extracurricular work). Were also studied the possibility of using the Arduino in a complex innovation activities of students, that takes place in the educational process in physics. Under this activity we understand the variety of their educational activities, organized by teacher and it runs a specially crafted learning environment and related to creation, theoretical and experimental research and implementation in practice (e.g. at educational process in school, at scientific laboratories, enterprises) certain news (device or method) that provides a useful effect of its use. These studies have shown that the hardware-software complex Arduino can play the important extracurricular training cognitive activity of future teachers of Physics and students (in particular for enhance their research and innovation activities). It indicates the usefulness of this complex for future teachers of Physics in the process of their professional training at the University. The article also gives the examples of using Arduino in the demo experiment in Physics and in the process of students’ innovation activities. In particular, we consider the experimental task, a possible solution. It provides automation of physical experiment, and provides innovative products. created by the students and the students of the experimental group